Benefits of IUD Family Planning for Mothers' Participation at Hana Kasih Clinic in 2019 - Dwi Ris Hasanah; Arva Rochmawati (Institute of Computer Science (IOCS), 2019)
The purpose of this study was to increase the knowledge and insight of mothers of IUD family planning acceptors about reproductive health and family planning, that the IUD is the most effective long-term contraceptive for spacing pregnancies or terminating pregnancies. And the activities carried out to increase the knowledge of IUD acceptor mothers that this contraceptive is a long-term contraceptive method that can space the number of children, or stop pregnancy. Increasing the knowledge of IUD family planning acceptors also has advantages and disadvantages for its users. The types and forms of activities of this activity are the provision of material to mothers of IUD family planning acceptors about the meaning, types of IUDs, benefits, advantages, disadvantages of using contraceptives, and side effects of using IUDs. Health checks, such as measuring maternal blood pressure and others. Results To achieve the objectives of the above activities, activities were carried out, including providing material to mothers of IUD family planning acceptors about the meaning, types of IUDs, benefits, advantages, disadvantages of using contraceptives, and side effects of using IUDs. And explain to the mother that the IUD is the most effective contraceptive method for spacing pregnancies and terminating pregnancy